RETRACTED: Plumbagin Ameliorates Collagen-Induced Arthritis by Regulating Treg/Th17 Cell Imbalances and Suppressing Osteoclastogenesis - Wang, Tingyu; Qiao, Han; Zhai, Zanjing; Zhang, Jun; Tu, Jinwen; Zheng, Xinyi; Qian, Niandong; Zhou, Hong; Lu, Eryi; Tang, Tingting (Frontiers in Immunology, 2019)
Objective: Plumbago zeylanica L. (with plumbagin as its active ingredients) has been used for centuries to treat conditions such as joint swelling, fractures and bacterial infections, suggesting that it possesses anti-inflammatory and immunosuppressive properties. In the present study, we evaluated the potential anti-arthritic activity and related mechanisms of plumbagin. Methods: Collagen-induced arthritis (CIA) was initiated in Wistar rats with collagen type II. Plumbagin (2 and 6 mg/kg) was orally administered to rats with CIA from day 12 to day 32 post immunization. The effects of plumbagin on arthritis progression were assessed by paw swelling, clinical scoring and histologic analysis. The percentage of Treg and Th17 were defined by flow cytometry or immunofluorescence (IF) staining. Bone erosion and resorption were assessed by micro-CT and histomorphometric analysis. Osteoclast differentiation was further determined by in vitro osteoclastogenesis assay. The molecular docking assay was used to determine the potential binding site of plumbagin. Results: Treatment with plumbagin significantly inhibited arthritis development, as well as suppressed the local and systemic inflammation. Plumbagin reciprocally regulated pro-inflammatory Th17 cell and immunosuppressive Treg cell populations. In addition, plumbagin protected inflammation-induced bone loss by inhibiting osteoclast formation and activity. Plumbagin markedly suppressed RANKL-stimulated osteoclast-specific gene expression by repressing NF-κB signaling activation and MAP kinase phosphorylation. Further study via molecular docking assay demonstrated that plumbagin bound to MET169 of JNK kinase and LYS138 and SER183 of p38 kinase. Conclusion: Plumbagin not only attenuates the immune-induced arthritis by inhibiting inflammation, but also protects bone erosion by directly inhibiting osteoclast formation and activity. These data suggest plumbagin is a promising new candidate drug for treating inflammatory joint diseases.